Answer:
x = 2.1
Explanation:
Solve for x:
0.4 (2 x + 0.3) = (6 x - 7.2)/3
Multiply both sides by 3:
3×0.4 (2 x + 0.3) = (3 (6 x - 7.2))/3
(3 (6 x - 7.2))/3 = 3/3×(6 x - 7.2) = 6 x - 7.2:
3×0.4 (2 x + 0.3) = 6 x - 7.2
3×0.4 = 1.2:
1.2 (2 x + 0.3) = 6 x - 7.2
Expand out terms of the left hand side:
2.4 x + 0.36 = 6 x - 7.2
Subtract 6 x from both sides:
(2.4 x - 6 x) + 0.36 = (6 x - 6 x) - 7.2
2.4 x - 6 x = -3.6 x:
-3.6 x + 0.36 = (6 x - 6 x) - 7.2
6 x - 6 x = 0:
0.36 - 3.6 x = -7.2
Subtract 0.36000000000000004` from both sides:
(0.36 - 0.36) - 3.6 x = -0.36 - 7.2
0.36 - 0.36 = 0:
-3.6 x = -0.36 - 7.2
-0.36 - 7.2 = -7.56:
-3.6 x = -7.56
Divide both sides of -3.6 x = -7.56 by -3.6:
(-3.6 x)/(-3.6) = (-7.56)/(-3.6)
(-3.6)/(-3.6) = 1:
x = (-7.56)/(-3.6)
(-7.56)/(-3.6) = 2.1:
Answer: x = 2.1